2016
DOI: 10.7201/earn.2016.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Testing for bubbles in agriculture commodity markets

Abstract: ABSTRACT:We apply the recent generalized sup augmented Dickey-Fuller (GSADF) test for explosive bubbles (Phillips et al., 2012) to monthly time-series for food, beverages, agricultural raw material, cereals, dairy, meat, oils and sugar indices and a total of 28 agricultural commodities between 1980-2012. We found price bubbles occurred for 6 out of the 10 indices studied and for 6 out of the 28 commodities within food markets. Results from the tests can help implementing policies aimed at mitigating effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
1
13
1
1
Order By: Relevance
“…In this 9 framework, the fundamental value of oil is defined as the sum of discounted oil dividends which are approximated by the convenience yield, see Lammerding, Stephan, Trede, and Wilfling (2013), Areal, Balcombe, and Rapsomanikis (2013) and Shi and Arora (2012)). …”
Section: Which Oil Price To Use?mentioning
confidence: 99%
“…In this 9 framework, the fundamental value of oil is defined as the sum of discounted oil dividends which are approximated by the convenience yield, see Lammerding, Stephan, Trede, and Wilfling (2013), Areal, Balcombe, and Rapsomanikis (2013) and Shi and Arora (2012)). …”
Section: Which Oil Price To Use?mentioning
confidence: 99%
“…If no bubble exists, i.e., = 0, the properties of are determined only by those of . However, if 0, current prices will exhibit an explosive behavior, as reflects a stochastic process in which the expected value of next period's value is greater than or equal to the current period's value (Areal et al, 2013). Therefore, we implement a right-tailed version of the standard ADF test for a unit root (which means = 0) against the alternative of an explosive root (…”
Section: Frameworkmentioning
confidence: 99%
“…For instance, Gilbert (2010) considers both monthly and daily nearby prices, finding evidence of bubbles in daily soybean prices but not in monthly prices. Areal et al (2014) attribute the lack of bubbles found in some commodities in their paper partly to the low-frequency of the data (monthly) used in the analysis. Second, from a policy perspective, lower-frequency data may be preferred as policy initiatives tend to be made over a longer horizon.…”
Section: Datamentioning
confidence: 94%
“…Daily prices are considered in Gutierrez (2013) and Etienne et al (2014Etienne et al ( , 2015, and monthly prices are used in and Areal et al (2014). Both of these frequencies are considered in Gilbert (2010).…”
mentioning
confidence: 99%